2010
DOI: 10.4314/ajbr.v11i2.50704
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of oral ascorbic acid (vitamin c) against acetaminophen- induced hepatic injury in rats

Abstract: The incidence of acetaminophen-induced hepatotoxicity is reported to be on the increase, with limited therapeutic or chemoprophylactic options. In the present in vivo study, single daily oral doses (100 -500 mg/kg) of ascorbic acid (ASC) were investigated for their protective effects against acetaminophen (APAP)-induced hepatotoxicity in 4 groups of rats made up of 6 rats per group for 14 days. Also, effects of the doses on body weights taken on the 1 st , 7 th and 15 th day of the experiment were also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…Vitamin C is considered to be an important antioxidant in extracellular fluid; it also guards against aqueous radicals in blood and protects plasma lipids from peroxidative damage caused by peroxyl radicals (BARJA et al, 1994). Furthermore, there are a few studies reporting the antioxidant power of vitamin C against different chemicals-induced oxidative tissue injury (CARR and FREI, 1999;ADENEYE and OLAGUNJU, 2008;HASSANIN et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C is considered to be an important antioxidant in extracellular fluid; it also guards against aqueous radicals in blood and protects plasma lipids from peroxidative damage caused by peroxyl radicals (BARJA et al, 1994). Furthermore, there are a few studies reporting the antioxidant power of vitamin C against different chemicals-induced oxidative tissue injury (CARR and FREI, 1999;ADENEYE and OLAGUNJU, 2008;HASSANIN et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C has been reported to be nephroprotective (Adeneye and Olagunju, 2009). The antioxidant potentials of vitamin C enable it to scavenge free radicals generated by chemical substances which would have damaged specific cells in the kidney tissues (Markowitz and Perazella, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Both human Idogun and Ajala (2005) [101] and animal Odigie et al (2007) [102] studies have shown ascorbic acid to be a potent antioxidant which mediates its antioxidant effect by scavenging free reactive oxygen radicals before reaching to the renal. The nephroprotection of ascorbic acid (oral 100-500 mg/kg) in acetaminophen induced nephrotoxic rats which is characterized by marked elevation of serum urea and creatinine, could be due to its inherent antioxidant effect by inhibition of free radicals generation and/or free radical scavenging activity [103].…”
Section: Resultsmentioning
confidence: 99%